2014
DOI: 10.1186/s40359-014-0050-3
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of illness perception to psychological distress in heart failure patients

Abstract: BackgroundThe influences on the psychological well-being of heart failure (HF) patients have received limited attention. Illness perceptions are a specific set of cognitive representations that have been shown to predict health-related outcomes in other patient groups. This study sought to explore the role of illness perceptions in the psychological well-being of HF patients by creating a profile of illness perceptions in HF and examining their relations with anxiety and depression.MethodsParticipants were 95 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 49 publications
5
29
0
1
Order By: Relevance
“…Beliefs about consequences comprise effects of the illness on daily life, whereas cure/control beliefs contain perceived possibilities to cure or to control the condition through treatment or personal behavior [ 10 , 11 ]. The common sense model is widely used and empirically confirmed among patients with somatic diseases [ 12 , 13 ] and among patients with depression [ 14 19 ]. In patients with heart diseases, it has been shown that illness beliefs about heart failure are associated with psychological well-being [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beliefs about consequences comprise effects of the illness on daily life, whereas cure/control beliefs contain perceived possibilities to cure or to control the condition through treatment or personal behavior [ 10 , 11 ]. The common sense model is widely used and empirically confirmed among patients with somatic diseases [ 12 , 13 ] and among patients with depression [ 14 19 ]. In patients with heart diseases, it has been shown that illness beliefs about heart failure are associated with psychological well-being [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these items did not appear internally consistent within the Brief IPQ. This has also been observed in other studies (Morgan, Villiers-Tuthill, Barker, & McGee, 2014) and the items have shown variable ability to predict distress (Hagger & Orbell, 2003), which might suggest a limitation to the contribution of coping appraisals (and the self-regulatory model) in some populations, including HSCT. However, the complexity of HSCT, heterogeneity of care (Copelan, 2006), and social desirability when rating helpfulness of treatment (treatment control) may have introduced complexity in these appraisals that was not possible to capture in the current research.…”
Section: Perceptions Of Hsct and Copingmentioning
confidence: 65%
“…Korábbi tanulmányokban sikeresen alkalmazták többek között szívbetegségek, reumás arthritis, tumoros megbetegedések, psoriasis és diabetes mellitus esetén [9,10,11], azonban IBD-ben még nem vizsgálták. A betegségidentitás-faktort 14, gyakran ész-lelt tünet előfordulásának vizsgálatával méri, mint példá-ul fájdalom, émelygés, légszomj, testsúlyváltozás, kimerültség.…”
Section: Ipq-runclassified